The efficacy of misoprostol vaginal insert compared with oral misoprostol in the induction of labor of nulliparous women: A randomized national multicenter trial. (12th March 2019) - Hokkila, Emma; Kruit, Heidi; Rahkonen, Leena; Timonen, Susanna; Mattila, Mirjami; Laatio, Liisa; Ordén, Maija‐Riitta; Uotila, Jukka; Luukkaala, Tiina; Tihtonen, Kati
Abstract: Introduction: Our objective was to compare the efficacy of a 200‐μg misoprostol vaginal insert vs oral misoprostol regarding the cesarean section rate and the time interval to vaginal delivery in nulliparous women with unfavorable cervix. Material and methods: In this prospective multicenter trial, 283 nulliparous women at term with Bishop score <6 were randomized to induction of labor with either a misoprostol vaginal insert (n = 140) or oral misoprostol (n = 143). In the oral misoprostol group, a 50‐μg dose of oral misoprostol was administered every 4 hours up to three times during the first day; during the second day, the dose was increased to 100‐μg every 4 hours up to three times during the first day, if necessary. Primary outcome was the cesarean section rate. Secondary outcomes were the time from induction of labor to vaginal delivery, the rate of other induction methods needed, labor augmentation with oxytocin and/or amniotomy, use of tocolytics and adverse neonatal and maternal events. Results: In the misoprostol vaginal insert group, median time to vaginal delivery was shorter (24.5 hours vs 44.2 hours, P < 0.001), whereas no difference was found in the cesarean section rate (33.8% vs 29.6%, odds ratio [OR] 1.21, 95% confidence interval [CI] 0.66‐1.91, P = 0.67). Other induction methods and labor augmentation with oxytocin and/or amniotomy were less frequent in the misoprostol vaginal insert group (OR 0.32, 95% CI 0.18‐0.59 and OR 0.56, 95% CI 0.32‐0.99, respectively). Need for tocolysis and meconium‐stained amniotic fluid were more common in the misoprostol vaginal insert group (OR 3.63, 95% CI 1.12‐11.79 and OR 2.38, 95% CI 1.32‐4.29, respectively). Maternal and neonatal adverse events did not differ between groups. Conclusions: Misoprostol vaginal insert proved to shorten the time to vaginal delivery and to reduce the use of other methods of labor induction and augmentation, but it did not reduce the cesarean section rate compared with oral misoprostol. The benefit of more rapid delivery associated with misoprostol vaginal insert should be weighed against the greater risks for uterine hyperstimulation and meconium‐stained amniotic fluid.